Frameworks for evaluation of community health centers' services and outcomes: a scoping review protocol. (April 2019) - Nagel, Daniel A.; Keeping-Burke, Lisa; Pyrke, Ryan J.L.; Pyrke, Courtney L.B.; Goudreau, Alex; Luke, Alison; Wilbur, Kimberly A.; Waycott, Loretta; Hamilton, Catherine
Abstract : Review objectives/question: The objective of this scoping review is to identify and map the frameworks used to evaluate services and outcomes of community health centers within the broader context of primary health care. The primary question for this scoping review is: what are the frameworks used to evaluate services and outcomes of community health centers? Secondary questions for this review are: How is the concept community health center defined or described in the literature? What services and/or elements comprise a community health center? How are services and outcomes for a community health center evaluated?